2020
DOI: 10.1007/s11224-020-01682-x
|View full text |Cite
|
Sign up to set email alerts
|

On the aromaticity of uracil and its 5-halogeno derivatives as revealed by theoretically derived geometric and magnetic indexes

Abstract: The problem of aromaticity in heterocyclic rings of uracil and its 5-halogenoderivatives (5XU) was analyzed theoretically by calculating modified harmonic oscillator model of aromaticity (HOMA) for Heterocycle Electron Delocalization (HOMHED), nucleus-independent chemical shift parameters (NICS) and the so-called scan experiments, using helium-3 atom as a magnetic probe. The impact of halogen electronegativity on C5 atom’s NBO charges was also investigated. Water, as a polar environment, has a negligible impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Uracil is an important component related to information transfer and replication in living systems. Its 5-halogen modifications are used in anticancer and antifungal treatment [ 59 , 61 , 62 , 63 ]. Modifications of uracil, including replacing the oxygen atom with sulfur [ 64 ], also changes its biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Uracil is an important component related to information transfer and replication in living systems. Its 5-halogen modifications are used in anticancer and antifungal treatment [ 59 , 61 , 62 , 63 ]. Modifications of uracil, including replacing the oxygen atom with sulfur [ 64 ], also changes its biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Aromaticity of uracil and its 5-chalogen derivatives were tested using GIAO NMR calculations of NICS magnetic indexes. 126 Kleinpeter and Koch employed NICS calculation for testing the nature of carbon-boron bond in boron trapped N-heterocyclic carbenes. 127 In addition, Kleinpeter et al 128 reported on a 29 Si and 13 C NMR conformational equilibrium study of 1-phenyl-1-tert-butylsilacyclohexane.…”
Section: Other Examples Of Nuclear Shielding Modelingmentioning
confidence: 99%
“…1a, is most stable. [16][17][18][19] According to X-ray studies, uracil is found only in the diketo form in the solid phase, and in the same form, it exists in water. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%